Association between hypertension and osteoarthritis: A systematic review and meta-analysis of observational studies - Kenneth Lo (Elsevier, 2022)
Objective: Literature examining the relationship between elevated blood pressure and osteoarthritis (OA) has yielded conflicting results. This study aimed to systematically review the relationship between hypertension and OA in both load-bearing and non-load-bearing joints. Methods: A systematic literature search was performed on Embase, Emcare, MEDLINE and Ovid Nursing Database. The associations between hypertension and OA development in knees, hips and hands were analysed by calculating the odds ratio (OR). Results: A total of 26 studies with 97,960 participants were included. The overall odds of having OA significantly increased in the people with hypertension compared to the normotensive ones (OR ​= ​1.60, 95%CI ​= ​1.33, 1.94). The association of hypertension with OA was detected in knee (OR ​= ​1.62, 95%CI ​= ​1.32, 1.98), not in hand (OR ​= ​1.19, 95%CI ​= ​0.92, 1.53). Moreover, there existed a stronger association of hypertension with radiographic knee OA (OR ​= ​1.89, 95%CI ​= ​1.40, 2.54) than symptomatic knee OA (OR ​= ​1.39, 95%CI ​= ​1.17, 1.65). The association between hypertension and radiographic knee OA remained statistically significant for the studies that adjusted for body mass index (BMI) (OR ​= ​1.42, 95%CI ​= ​1.13, 1.78), and was particularly strong in women (OR ​= ​2.27, 95%CI ​= ​1.17, 4.39). Conclusion: A BMI-independent association between hypertension and radiographic knee OA existed with potential sex variation, which warrants further investigations into the underlying genetic, hormonal and environmental factors.The translational potential of this article: Blood pressure has been reported to link with OA for years ago, however, its contribution to OA is still unclear and conflicted in different reports. This review indicated an intimate relationship between hypertension and structural damages of knee OA, rather than simply chronic joint pain, especially in women. This finding not only provides stronger support for further investigations into the causal risk factor, i.e. hypertension, of OA from tissue level to molecular level, but also putting forward a novel thinking in OA pathogenesis and its therapy strategies. Orthopedic translation: This study further strengthen the association between hypertension and radiographic knee OA. It points in a vascular aetiology hypothesis of OA. It might open up a new avenue for repositioning anti-hypertensive medications for osteoarthritis treatment.